Endothelial Dysfunction in Stable COPD: A Case-Control Evaluation of Flow-Mediated Dilatation and Its Clinical Correlates in Northern India - Dr Aseem Sirkeck; Dr Shagun; Dr Malay Sarkar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Endothelial dysfunction is considered a mechanistic bridge between chronic obstructive pulmonary disease (COPD) and its excess cardiovascular mortality. Objectives: (i) Quantify brachial-artery flow-mediated dilatation (FMD) in clinically stable COPD versus never-smoking controls; (ii) identify clinical correlates of impaired FMD within COPD. Methods: In this hospital-based case-control study (March 2019 – April 2020) 43 spirometry-confirmed COPD patients (≥ 6 weeks exacerbation-free) and 41 age-/sex-matched never-smokers underwent ultrasound FMD (10 MHz probe, forearm occlusion 200 mmHg × 5 min). Endothelial dysfunction was predefined as %ΔFMD < 4 %. Multivariable logistic regression adjusted for age, body-mass index and smoking index. Results: Mean %ΔFMD was halved in COPD (21.7 ± 8.2 %) compared with controls (41.7 ± 5.8 %, p < 0.001). Endothelial dysfunction affected 79.1 % of COPD patients versus 12.2 % of controls (OR = 30.4, 95 % CI 11.1–82.7). Within COPD, lower FMD correlated with FEV₁ %-predicted (r = 0.41, p = 0.006), resting SpO₂ (r = 0.35, p = 0.02) and CAT score (r = –0.38, p = 0.01). Each 10 % decrement in FMD independently predicted GOLD 3/4 severity (adjusted OR = 1.9, 95 % CI 1.2–3.5). Conclusions: Northern-Indian COPD patients exhibit marked endothelial dysfunction proportional to airflow limitation and symptom burden. A simple FMD threshold (< 25 %) discriminates GOLD ≥ 3 disease with good accuracy and could enrich cardiovascular risk stratification in routine pulmonary clinics. Longitudinal trials should test whether interventions targeting systemic inflammation, hypoxaemia or oxidative stress restore endothelial function and reduce downstream vascular events.